2020
DOI: 10.1002/hbm.25288
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurophysiological signatures of interoceptive enhancements following vagus nerve stimulation

Abstract: An accruing body of research has shown that interoception (the sensing of signals from the body's internal milieu) relies on both a direct route (afforded by the vagus nerve) and a secondary route (supported by somatosensory mechanisms). However, no study has causally tested the differential role of these pathways, let alone via direct stimulation. To bridge this gap, we tested whether multidimensional signatures of interoception are modulated by noninvasive vagus nerve stimulation (nVNS). Sixty‐three particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 123 publications
(252 reference statements)
4
16
1
Order By: Relevance
“…Richter, et al (2020) used the GammaCore device (ElectroCore, LLC) to transcutaneously stimulate the cervical vagus nerve in a between-subjects design 81 . Substantial methodological differences make it difficult to directly compare the present results with Richter and colleagues' report.…”
Section: Discussionmentioning
confidence: 99%
“…Richter, et al (2020) used the GammaCore device (ElectroCore, LLC) to transcutaneously stimulate the cervical vagus nerve in a between-subjects design 81 . Substantial methodological differences make it difficult to directly compare the present results with Richter and colleagues' report.…”
Section: Discussionmentioning
confidence: 99%
“…Several short-duration WI protocols all increased HR variability (HRV), and the greatest impact of WI on HRV is on the high-frequency (HF) component, indicating a shift toward enhanced parasympathetic nervous activity [ 61 , 62 ]. A previous study using transcutaneous auricular vagus nerve stimulation (taVNS), which stimulates the vagus nerve noninvasively and inhibits sympathetic nervous activity, revealed that interoception significantly improved after this stimulation, although cardiac sympathetic nervous activity returned to baseline levels [ 63 ]. The authors explained that taNVS could activate the insular cortex, which modulates interoception.…”
Section: Discussionmentioning
confidence: 99%
“…For the tapping-priming phase, we used a validated heartbeat detection (HBD) task ( Canales-Johnson et al, 2015 ; García-Cordero et al, 2016 ; Yoris et al, 2017 , 2018 ; Salamone et al, 2018 , 2020 ; Abrevaya et al, 2020 ; Richter et al, 2021 ; Richter and Ibáñez, 2021 ). Participants were required to tap a computer keyboard along with their heartbeats (Intero) or external stimuli (Extero).…”
Section: Methodsmentioning
confidence: 99%